How can safety nets do more with less?: general issues with some evidence from Southern Africa - Haddad, Lawrence J.; Zeller, Manfred (International Food Policy Research Institute, 1996)
This paper reviews design features by which safety nets might do more with less. It reviews the current evidence on their success in practice–including three brief reviews of southern Africa experience–and suggests a role for future policy research in furthering the goal of designing safety nets that reduce poverty in a cost-effective way. In doing so, the paper highlights a tension between the large gaps in our knowledge about the design of safety nets and the demand for short-run answers in this area.